Transformation Of The MSMe Business Of Processed Chicken Grilled Today Through Digital Media Based Marketing Communications - Muh. Husriadi; Bunga Kartika; Usman. M Usman. M; Amos Amos (PT. Anagata Sembagi Education, 2024)
This study discusses the business transformation of the Modern Fried Chicken MSME through digital media-based marketing communication strategies amidst increasingly tight competition and technological developments. The purpose of this study is to examine the impact of using social media, such as Instagram and Facebook, on increasing brand awareness, customer interaction, and loyalty and sales. This study uses a qualitative method with a case study approach on the Modern Crushed Chicken UMKM, with data collection techniques in the form of in-depth interviews and digital content analysis. The results of the study show that the use of social media effectively increases market reach, customer engagement, and contributes directly to increasing short-term sales and long-term customer loyalty. This finding emphasizes the importance of adopting digital communication strategies in supporting the growth of MSMEs in the digital era. The implications of this research provide practical insights for MSMEs in utilizing digital technology to strengthen competitiveness and improve business performance.